การพัฒนารูปแบบพยาบาลพี่เลี้ยงเพื่อเตรียมพยาบาลวิชาชีพเข้าสู่ตำแหน่งหัวหน้าหอผู้ป่วย โรงพยาบาลเอกชน - กัญญารัตน์ จูงพิริยะพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purposes of this research and development study were: 1) to synthesize nurse mentorship model in preparation for professional nurses to be head nurse position, 2) to study effectiveness of self-confidence of head nurse role, and 3) to evaluate effect after using nurse mentorship model. Participants were 8 head nurses who were mentored nurses and 8 professional nurses from the same ward as mentored nurses for being nurse mentorship model at Samitivej Srinakarin Hospital. The instruments for the test included mentor handbook, mentor weekly plan, and mentor training project. The instruments for supervision test included mentor activity’s record and mentor learning’s evaluation form. Research data was obtained from professional nurse’s self- confidence form and group questionnaires. All instruments were tested for validity by groups of experts. Data was tested and analyzed after using nurse mentorship model for preparing professional nurses to be promoted to head nurse position. Major findings were as follows : 1. Nurse mentorship model which was consisted of preparing for nurse mentor, activities for preparing profession nurse to be head nurse and evaluation of activities. 2. After using nurse mentorship model for preparing professional nurses to be promoted to head nurse position, professional nurses had shown high level of their confidential on head nurse roles performance. (x = 3.72, SD = 0.09)